Teachings from the prelates of Castile about the Christian doctrine - Teodoro, Leandro Alves [UNESP] (OpenEdition, 2020)
Between the middle of the fourteenth century and the end of the fifteenth, the bishops of Castile intensified the proposal to make the synods a place for the implementation of rules that could help all sorts of people to correct their faults and, consequently, to absorb the rudiments of Christian doctrine. Through the examination of a part of the synodical constitutions of this period, this work seeks to analyze the role of the prelates in the promotion of teachings to be memorized by any type of churchgoer, regardless of their origin or social condition.
Lições dos prelados de Castela sobre a doutrina cristã
Les leçons des prélats de Castille sur la doctrine chrétienne
Keywords: Bishops; Castile; Christian customs; Councils and synods; Fifteenth centuries; Fourteenth; Rudiments of faith